ANALISIS KADAR TOTAL METABOLIT SEKUNDER EKSTRAK ETANOL DAUN TAMOENJU (Hibiscus surattensis L.) - Astrid Natalia Alasa; Syariful Anam; Jamaluddin Jamaluddin (KOVALEN: Jurnal Riset Kimia, 2017)
Tamoenju (Hibiscus surattensis L.) leaves are included in the malvaceae family which grows in the plateau and are known to have the antidiabetic activity that the standardization of the extract is needed to be conducted. The research aimed to discover the total level of secondary metabolites from ethanol extract. The extraction of Tamoenju leaves through maceration method with 96% ethanol was done to obtain the filtrate. The filtrate obtained was concentrated by using rotary evaporator at 40°C until the concentrated extract was obtained. The extract gained was then tested in a qualitative way with Alkaloid, Flavonoid, Saponin, and Tannin tests by using the suitable reagent for the test parameters. While in the quantitative test the method used was Gravimetric analysis on alkaloid and Saponin compounds, Permanganometry on Tannin compound, and UV-Visible Spectrophotometry on Flavonoid. The qualitative test results reveal that Tamoenju is positive for containing Alkaloid which was characterized by the presence of orange sediment, Flavonoid was characterized by the orange formation, Tannin was characterized by the dark blue and Saponin was characterized by the stable foam. The quantitative test results are Alkaloid by 305.181 g/g, Saponin by 371.112 g/g, Tannin by 55.417 g/g and Flavonoid by 14.999 mg/100 g.Keywords: Hibiscus surattensis L. , secondary metabolites, standardization